The Youth Olympic Games: the best of the Olympics or a poor copy? - Hanstad, D. V.; Parent, M. M.; Kristiansen , E. (European Sport Management Quarterly, 2013)
This paper explores the new event in the Olympic Movement, the Youth Olympic Games (YOG) in Innsbruck, Austria, in 2012, and examines the similarities and differences between the winter editions of the YOG and the Olympic Games (OG). The qualitative case study utilised a stakeholder approach and revealed four main groupings that differed in relative salience as compared to the OG: the host core stakeholders, international core stakeholders, sponsors and media, and parents and other stakeholders. From an external perspective, the YOG had the general ?look-and-feel? of the OG, despite their smaller size and relatively lesser involvement by sponsors and the media. However, this may have helped showcase the Olympic Movement tenets like those presented in the Culture and Education Programme. The YOG were thus closer to the Olympic ideals than the OG. We further discuss this and other paradoxes and disconnects requiring further debate and analysis. This paper explores the new event in the Olympic Movement, the Youth Olympic Games (YOG) in Innsbruck, Austria, in 2012, and examines the similarities and differences between the winter editions of the YOG and the Olympic Games (OG). The qualitative case study utilised a stakeholder approach and revealed four main groupings that differed in relative salience as compared to the OG: the host core stakeholders, international core stakeholders, sponsors and media, and parents and other stakeholders. From an external perspective, the YOG had the general "look-and-feel" of the OG, despite their smaller size and relatively lesser involvement by sponsors and the media. However, this may have helped showcase the Olympic Movement tenets like those presented in the Culture and Education Programme. The YOG were thus closer to the Olympic ideals than the OG. We further discuss this and other paradoxes and disconnects requiring further debate and analysis.